2011
DOI: 10.1667/rr2084.1
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interactions Occur Between p53 Phosphoforms and ATM and 53BP1 at Sites of Exogenous DNA Damage

Abstract: We have previously shown that the Ser15-phosphorylated p53 phosphoform, p53(Ser15), can localize at sites of ionizing radiation-induced DNA damage. In this study, we hypothesized that the non-specific DNA binding domain (NSDBD) of the p53 carboxy-terminus (C-terminus) mediates chromatin anchoring at sites of DNA damage to interact with two key mediators of the DNA damage response (DDR): ATM and 53BP1. Exogenous YFP-p53 fusion constructs expressing C-terminus deletion mutants of p53 were transfected into p53-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…KU0055933 (ATM-i) is a specific inhibitor of ATM kinase and is 100 times more potent against ATM than any other phosphatidylinositol-3-like kinase (Hickson et al, 2004). We have previously shown that 10 mM ATM-i decreases the phosphorylation of ATM substrates under oxic conditions (Al Rashid et al, 2011;Fraser et al, 2011). Control Fig.…”
Section: G0-g1 Synchronized Fibroblasts Represent a Robust Model To Smentioning
confidence: 99%
“…KU0055933 (ATM-i) is a specific inhibitor of ATM kinase and is 100 times more potent against ATM than any other phosphatidylinositol-3-like kinase (Hickson et al, 2004). We have previously shown that 10 mM ATM-i decreases the phosphorylation of ATM substrates under oxic conditions (Al Rashid et al, 2011;Fraser et al, 2011). Control Fig.…”
Section: G0-g1 Synchronized Fibroblasts Represent a Robust Model To Smentioning
confidence: 99%
“…13,29 For experiments requiring quantification, maximum intensity projections of at least 50 nuclei were counted in three separate experiments using Image Pro Plus software (Media Cybernetics) and manually determined thresholds for foci identification were used and maintained throughout each experiment. The fold foci induction was calculated as the ratio of foci number for the IR-treated cells to the foci number for unirradiated cells, errors presented are SEM and 3D renderings were produced using Imaris software (Bitplane).…”
Section: Ser1981mentioning
confidence: 99%
“…10,[12][13][14][15] 53BP1 may also facilitate the specific repair of DSBs through direct stimulation of nonhomologous end-joining (NHEJ) and by suppressing homologous recombination (HR). [16][17][18][19] Unresolved DSBs can be visualized as late foci (unrepaired DSBs) at 24 h or more following activation of the DDR and lead to DDR-induced senescence, with 53BP1 protein juxtaposed to PML-NBs.…”
Section: Introductionmentioning
confidence: 99%
“…In response to DNA damage, molecular sensors such as ataxia telangiectasia mutated (ATM) can be activated, which initiate signal transduction pathways that lead to cell cycle arrest and allow time to correct the damage (Khanna et al, 2001). Activated ATM results activation of Chk1 and Chk2 by phosphorylation, and stabilizes p53 by phosphorylation (Al Rashid et al, 2011). Phosphorylation of Cdc25C, which is controlled by Chk1 and Chk2 activation, is involved in the G2/M transition (Bartek and Lukas, 2003).…”
Section: Discussionmentioning
confidence: 99%